(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
Stipa sibirica (L) is one of important perennial grass species which belong to genus of Stipa, and family of Poaceae. It has early growth in spring and good quality for animal productivity and good adaptability in vast range of sever conditions in all over the country. Temperature and drought stress are among the two most important environmental factors influencing crop growth, development and yield processes. This study compares three stresses which as cold, drought and saline conditions. In vitro stress assays are commonly used to study the responses of plants to abiotic stress and to assess stress tolerance. Exposure of plants to a drought stress for 10 days significantly decreased the photochemical efficiency of PSII and the Fv/Fm values were almost 50% lower (0.41±0.01) compared with the control plants (0.81±0.01).During cold stress after21 days Fv/Fm decreased to 0.40 ± 0.03. The results of this study demonstrated that Stipa sibirica (L) plants were better adapted to cold conditions than the drought conditions Journal of agricultural sciences №15 (02): 118-122, 2015